The best job in the world : how to make a living from following your dreams - Southall, Ben, 1975- (Wiley, 2015)
The true story of the man with the Best Job in the World The Best Job in the World is the story of how following your passions can lead to life-changing opportunities. Adventurer Ben Southall shares his experiences and lessons learned as the winner of the inaugural Tourism Queensland''s Best Job in the World campaign, and reveals how this has led to ongoing opportunities since. Part autobiography, part insight into the power of a unique marketing campaign, this book follows Ben''s journey-from leaving the UK on his own expedition around Africa to his new role as caretaker of Hamilton Island on.